Legal Certainty of Customary Land Certificates of the Minangkabau Customary Community in Solok Regency: Kepastian Hukum Sertifikat Tanah Ulayat Kaum Adat Minangkabau Di Kabupaten Solok - Channiago, Erin; Fidiyani, Rini (Annual Review of Legal Studies, 2024)
Minangkabau customary land is a high heritage that cannot be traded, communal ownership rights (shared), Customary land registration does not have regulations that require customary land to be registered, in government regulation No. 24 of 1997 concerning land registration. Customary land is not included in the object of registration. Considering that customary land registration is important as proof of ownership of land rights in accordance with one of the objectives of the UUPA in creating legal certainty, which aims to provide legal certainty and legal protection of people's land rights fairly and evenly. the community does not know whether customary land can be registered and land registration in whose name, and how to carry out customary land registration. The community's assumption in the customary land registration process requires time and a complicated process and expensive costs. The conclusion of this study is first, customary land registration can be with MKW and different ownership rights and requirements, second, there is a community goal of wanting to register customary land, third, there are obstacles in the customary land registration process both external and internal. Suggestions in this study (1) The Solok Regency Land Office can map the location in customary land registration, (2) conduct socialization related to customary land registration.